ANALYSIS OF PHYTOCONSTITUENT PROFILE OF FENUGREEK –TRIGONELLA FOENUEM-GRAECUM L. - SEED EXTRACTS - VÍGH, Szabolcs; CZIÁKY, Zoltán; SINKA, László Tamás; PRIBAC, George Ciprian; MOŞ, Liana Mioara; TURCUŞ, Violeta; REMENYIK, Judit; MÁTHÉ, Endre (Studia Universitatis Babeș-Bolyai Chemia, 2017)
Fenugreek (Trigonella foenum-graecum L.) is a well-known herb for its efficiency in the prevention/treatment of diabetes among other chronic diseases. The aim of present study was to analyse the phytoconstituent profile of aqueous and hydro-alcoholic extracts of fenugreek seeds produced in Hungary. The aqueous and hydro-aqueous extracts were analysed using a UHPLC-ESI-MS approach, and in the first 54, while in the second extract 67 phytoconstituents were identified that mostly corroborate the previously described health promoting effects of fenugreek. However, it remains a huge challenge to correlate the phytoconstituent composition of the two extracts with the generated dose dependent hormetic response and cytotoxic effects that were reported by us in case of some human breast cancerous cell lines.